Professor fazedor de currículos: desafios no estágio curricular supervisionado em ensino de Física - Hunsche, Sandra (2010)
In the face of current educational problems, indicated by research, as the propedeutic education and the separation between the "world of life" and the "world of school," the conception of science and technology neutral, among others, it is necessary to "make changes" in curriculum. Moreover, it is argued that teachers should be part of the process of curriculum reconfiguration. So, in this research, it is looked for identify and critically analyze challenges and potential faced by trainees in physics in the process of reconfiguring a curriculum guided by the approach of social themes marked by the Science and Technology. More specifically, focus on the elaboration and implementation of themes under the Supervised Internship Course in Teaching of Physics. The structure of these themes is referenced by an approximation of the presuppositions of the educator Paulo Freire and the Science-Technology-Society movement (CTS). The research problem is characterized by the following questions: 1) What dimensions the school context influences the execution of curriculum reconfigurations based on themes? 2) What are the constraints that the training of future teachers, has in the process of elaboration/implementation of themes? The research, entered on the Research Line called School Practice and Public Policies (PPGE/UFSM), is developed according to the dynamics of participative research. The instruments to obtain the "data" were used the Teacher's Journal, a semi-structured interviews and analysis of reportsfiled by the student teacher. The analysis was done using content analysis. The results were organized under four thematic categories: Training Fragmented; From Rigor" to the Curricular Flexibility; Real Problems and Epistemological Curiosity, and Student Problem or Curriculum Problem?.